The temptation of utopia - Luque Mogrovejo, Rolando (2006)
There is a phrase that the rebellious youth of May 1968 repeated in the streets and squares of Paris, perhaps oblivious to the dangerous implications of its meaning: "let's be realistic, let's ask for the impossible." It is probable that the original desire of this phrase was to dramatize on the public stage, appealing to the paradox of assigning concreteness to the limitless dimension of his political and cultural dreams. Without a doubt, a valid clamor in the midst of the libertarian choreography of that time. But, set in history, the phrase summarizes, with incredible precision, the disturbing ideology of any utopia.